A real-world study of adverse drug reactions of two isocitrate dehydrogenase inhibitor based on the US FDA adverse event reporting system and VigiAccess databases - Peng, Mengmeng; Guo, Qian; Dang, Zihan; Zhang, Baiquan; Li, Manjuan; Wang, Zixuan; Lu, Xuemian; Lin, Jie (Frontiers in Pharmacology, 2024)
Background and objectives: Isocitrate dehydrogenase (IDH) inhibitor drugs (Enasidenib, Ivosidenib) restore normal metabolism and epigenetic regulation in cells, offering a precision-targeted therapeutic option for acute myeloid leukemia( AML) patients with IDH mutations by specifically inhibiting mutated IDH enzymes. This research evaluates the relationship between adverse drug reactions (ADR) and the use of two isocitrate dehydrogenase inhibitors by using the database from the World Health Organization (WHO) VigiAccess and compares the characteristics of ADRs of the two drugs.Methods: This study design used the retrospective descriptive analysis. We calculated the ratio of ADRs recorded in reports to compare the same points and different points in ADRs between two medications. Proportional reporting ratio (PRR) and reported odds ratio (ROR) were used to evaluate the relationship between these two isocitrate dehydrogenase inhibitor medications and adverse events.Results: Overall, during the search, 4072 adverse events (AE) related to two types of isocitrate dehydrogenase inhibitors were reported in VigiAccess. The results revealed that the top 10 most common AEs were off label use, death, fatigue, nausea, diarrhea, acute myeloid leukemia, drug ineffective, differentiation syndrome, platelet count decreased and decreased appetite. Compared two drugs, enasidinib had the highest adverse reaction reporting rate in general disorders and administration site conditions while ivosidenib had the highest ADR reporting rate in injury, poisoning and procedural complications.Based on the current comparative observational studies, the ADR reports received by the World Health Organization, Food and Drug Administration for these drugs list common and specific adverse drug reactions. Clinical doctors should develop individualized treatment plans based on the adverse reactions of different drugs and the specific conditions of patients to promote the rational use of these expensive medications.